THE EFFECTIVENESS OF PRACTICUM KIT AS A LEARNING MEDIA TO TRAIN SPS ON REACTION LAW - Trimayanto, Sigit; Novita, Dian (Universitas Negeri Surabaya, 2019)
This study aims to produce the Practical KIT along with its devices that are effectively used as learning media to train students SPS on the sub material of the Reaction Rate Law. The method used in this study is Research and Development design. The research instrument used consisted of a sheet of pre-test and post-test. Data analysis was carried out in descriptive quantitative to determine the effectiveness of Practical KIT along with the devices developed. The media is said to be effective if it meets 2 requirements, namely the percentage of classical completeness <85% and N-gain value <0.3. The developed media has been declared effective as indicated by the increase in the value of cognitive learning outcomes in the